On selected issues of Boolean function application in symmetric key cryptography against side channel attacks - Seman K.; Roslan M.F.; Syam Mohd Sayuti M.N.A; Azni Hazlizan Ab Halim (Institute of Physics Publishing, 2024)
Indexed by SCOPUS/ERA